Effects on Morphometry of Small Intestine of Broiler (Gallus domesticus) by Using Various Feed Additives - Saini, Jyoti (Indian Journal of Veterinary Anatomy, 2018)
An experiment was conducted using 350 one-day old unsexed (Cobb 400) broiler chickens to study the effect of dietary supplementation of various feed additives on morphometric characteristics of small intestine. Experimental treatments were: 1) control, 2) control + cocktail enzymes, 3) control + prebiotic, 4) control + probiotic, 5) control + organic acid 6) control + antioxidant and 7) control + saponin and inulin. Results showed that body weight, small intestine weight, relative weight (%), small intestine length, weight to length ratio were significantly improved by the supplementation of feed additives (P<0.05). These data indicated that supplementation broiler diet with feed additives may stimulate growth at a later age and may facilitate broilers in reaching their target weight sooner. Therefore, it may be recommended as potential alternatives to antimicrobials in chicken diets, especially in grower and finisher feed, it may also offer a good alternative to improve poultry production.